Rancang Bangun Sistem Penyiraman Otomatis pada Tanaman Sawi dengan Sistem Irigasi Tetes untuk Lahan Pertanian Lereng Gunung Ungaran - Awaludin, Muchammad Adib; Utomo, Aryo Baskoro (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
Cultivating mustard greens requires maintaining the ideal soil moisture level within the range of 50% to 70% Relative Humidity (RH). To fulfill water requirements and preserve soil moisture, irrigation processes are essential. Historically, farmers have employed manual irrigation methods, such as flooding entire agricultural fields, leading to water wastage and requiring significant labor. This research aims to develop an automated irrigation system based on soil conditions to assist farmers in the irrigation process. The automated irrigation system operates by responding to soil conditions. It initiates irrigation when the soil is dry and automatically ceases when the soil becomes adequately moist. This system utilizes Arduino as the central control unit, soil moisture sensors as input devices, an LCD for monitoring, and a water pump for distributing water to the agricultural fields through drip irrigation. The research methodology follows engineering design principles and encompasses three stages: design, installation, and implementation. The design phase involves creating the system, programming, and designing the drip irrigation system. Installation entails assembling the components of the automated irrigation system, while implementation involves deploying the system in agricultural fields and conducting tests. The research findings indicate that the automated irrigation system effectively irrigates when soil moisture falls below 50% and halts when it reaches 70%. Calibration tests reveal a 2% variance between the capacitive soil moisture sensor and the Soil Moisture Meter. The water requirement for a single mustard greens plant to reach the ideal soil moisture level (50-70% RH) is approximately 150 ml.